Identifying emotions toward an overweight avatar in Virtual Reality: The moderating effects of visuotactile stimulation and drive for thinness - van der Waal, Nadine Elisa; van Bokhorst, Julie A. W.; van der Laan, Laura Nynke (Frontiers in Virtual Reality, 2022)
Virtual Reality technologies can be used to alter one’s body image by inducing ownership of an overweight virtual body. This illusion can possibly lead to both negative affective responses towards the virtual body, as well as perceptual changes of one’s own body size, which are both scarcely examined with regard to the embodiment of an overweight avatar. This study has the fundamental aim to investigate, among normal weight participants, whether negative affect towards the virtual body and changes in body size perception can be evoked when embodying an overweight virtual avatar. Additionally, it was investigated whether applying visuotactile stimulation (which is identified as a proxy for virtual body ownership by previous studies), and drive for thinness influenced the strength of these effects. A 2 (normal weight vs. overweight virtual body) X 2 (congruent vs. incongruent visuotactile stimulation) between-subjects design was employed, and participants’ drive for thinness was measured to test its potential moderating effect. ANOVA’s revealed that participants (N = 114) experienced significantly more negative affect towards the virtual body when embodying the overweight virtual body compared to the normal weight virtual body. Visuotactile stimulation did not moderate this effect, even though the manipulation of visuotactile stimulation worked as intended (i.e., the experience of ownership over the virtual body was significantly higher in the congruent compared to incongruent visuotactile stimulation condition). Additionally, participants with high drive for thinness did not experience significantly more negative affect than participants with low drive for thinness. Embodiment of an overweight avatar did not affect body size perceptions, neither did visuotactile stimulation nor drive for thinness moderate this effect. Knowing that embodiment of an overweight avatar results in negative affective responses towards the avatar, future studies could deepen our understanding of the role of negative affect in the transfer of emotions to the own body, and the interplay between negative affect towards the virtual body and body size perceptions.